The Impact of Social Communication on Employment Success for Adolescents with Autism Spectrum Disorders - Clavenna-Deane, Beth; Pearson, Mary; Hansen, Blake (Journal of the American Academy of Special Education Professionals, 2020)
This study evaluated the effectiveness of a social communication intervention for improving the social skills and employability of four adolescents with Autism Spectrum Disorders (ASD). A multiple baseline across participants design was used to investigate the effectiveness of social communication skill development on equitable exchange in social conversations in a school training setting and an employment setting. Components from the "Social Thinking" curriculum that taught social communication through development of verbal interactions using supportive comments, follow-up questions, and bridging comments were combined with peer modeling and self-evaluation to provide the components of the intervention. The findings indicated that growth occurred for three of the four participants in their use of the aforementioned social communication skills in the school training setting; further growth generalized for two of the four participants to the employment setting.